Analisa Pekerjaan Paket Preservasi Jalan Sebelat–Simpang DPRD (Tugu Hiu) Melalui E-Katalog - Priyo Supeno; Rezi Munizar; Mekarria Pangaribuan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The Sebelat–Simpang DPRD (Tugu Hiu) Road is one of the strategic transportation corridors in North Bengkulu Regency, Indonesia, supporting the distribution of goods, public mobility, and regional economic activities. Deterioration of pavement conditions due to aging infrastructure and increasing traffic volumes necessitates road preservation to maintain service performance. This study aims to analyze the implementation of the road preservation package through the Electronic Catalog (E-Catalog) procurement system by evaluating existing pavement conditions, work volume and activities, procurement cost efficiency, procurement time efficiency, and post-preservation pavement performance. A quantitative descriptive method with a case study approach was employed using field survey data and project technical documents. The results indicate that the initial pavement condition improved from a PCI of 52 and IRI of 6.8 m/km to a PCI of 84 and IRI of 3.1 m/km after preservation. The E-Catalog procurement mechanism reduced unit costs by 3.6–12.9% and shortened the procurement duration from 40 days to 12 days. Nevertheless, implementation remains constrained by the limited availability of suppliers and specific construction items within the electronic catalog.